Respuesta :

2A = 2xy + xz

2A - xz = 2xy + xz - xz

2A - xz = 2xy

( 2A - xz ) ÷ 2x = 2xy ÷ 2x

A/x - z/2 = y

Hi there!  

»»————- ★ ————-««

I believe your answer is:  

[tex]y = \frac{2A-xz}{2x}; x \neq 0[/tex]

»»————- ★ ————-««  

Here’s why:  

⸻⸻⸻⸻

[tex]2A = x(2y+z)\\\\\rightarrow x(2y+z)=2A\\\\\rightarrow\frac{x(2y+z)=2A}{x}\\\\\rightarrow 2y + z = \frac{2A}{x}\\\\\rightarrow 2y + z - z = \frac{2A}{x}-z\\\\\rightarrow 2y = \frac{2A}{x} - z\\\\\rightarrow\frac{2y = \frac{2A}{x} - z}{2}\\\\\rightarrow \boxed{y = \frac{2A-xz}{2x}}[/tex]

⸻⸻⸻⸻

»»————- ★ ————-««  

Hope this helps you. I apologize if it’s incorrect.